Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex - Sonnenberg, Rainer (Zootaxa, 2007)
Three new species of the genus Chromaphyosemion Radda, 1971 are described from the coastal plains of Cameroon. They are distinguished from the phylogenetically and geographically close congeneric species through diagnostic characters of male color patterns. Some remarks on recently described species are made and a phylogenetic hypothesis of all currently known described species and all but two undescribed forms of the genus Chromaphyosemion based on mitochondrial DNA sequences is given. The molecular data support the monophyly of this genus as previously stated on the basis of morphological data and allow a review of the Chromaphyosemion splendopleure complex, a taxonomically confusing group. All newly described species are endemic to Cameroon, contributing to the high diversity and endemicity of the nothobranchiids in this country.